Prognostic impact of indoleamine 2, 3-dioxygenase 1 (IDO1) mRNA expression on circulating tumour cells of patients with head and neck squamous cell carcinoma. Issue 3 (14th May 2020) - Economopoulou, Panagiota; Kladi-Skandali, Athina; Strati, Areti; Koytsodontis, George; Kirodimos, Efthymios; Giotakis, Evangelos; Maragoudakis, Pavlos; Gagari, Eleni; Maratou, Eirini; Dimitriadis, George; Kotsantis, Ioannis; Vagia, Elena; et al.
Abstract : Background: We sought to determine the prognostic role of indoleamine 2, 3-dioxygenase 1 ( IDO1 ) by evaluating IDO1 expression in circulating tumour cells (CTCs) at baseline and after completion of chemoradiotherapy in patients with locally advanced (LA) head and neck squamous cell carcinoma (HNSCC) treated with curative intent. Methods: In a prospective cohort of 113 patients with LA HNSCC, we evaluated expression of IDO1 in the EpCAM+ CTC fraction at baseline and after cisplatin chemoradiation. The prognostic value of combined programmed cell death ligand-1 ( PDL-1 ) and IDO1 expression was assessed. Results: IDO1 was significantly overexpressed at baseline compared with the post-treatment counterparts (p=0.007). IDO1 messenger RNA (mRNA) expression at baseline was associated with better survival in terms of progression-free survival (PFS) (HR=0.19, p=0.017). Post-treatment IDO1 mRNA levels were correlated with unfavourable prognosis in terms of overall survival (OS) (HR=3.27, p=0.008). Patients with combined decreased expression levels of PDL-1 and IDO1 after treatment exhibited superior PFS (p=0.043) and OS (p=0.021). Conclusions: Our results strongly suggest that IDO1 mRNA expression is an independent prognostic factor for clinical outcome. Our study provides useful information for future trials combining chemoradiation with immune checkpoint inhibitors and IDO1 inhibitors.